Pendampingan Penyusunan Laporan Keuangan Menggunakan Program Akuaja.id Berbasis Excel pada Toko Celine Perabot - Nainggolan, Yohanna Thresia; Winata, Michelle; Zahra, Nourma Revania; Chandra, Lovita Cicielia; Royan, Muhammad (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Most MSMEs (Micro, Small, and Medium Enterprises) have not yet understood the financial reporting recording system, one of which is Toko Celine Perabot, which does not record or prepare financial statements. As a result, this MSME faces difficulties in monitoring its financial condition, leading to challenges for the business owner in making decisions. To address this issue, this community service activity was carried out to provide assistance in recording and preparing financial reports using the Akuaja.id program based on Microsoft Excel. The method applied in this activity was direct, offline mentoring. The results obtained from this community service show that the mentoring successfully improved the business owner's understanding of the importance of financial management for MSME actors, as well as the practice of preparing financial reports using the Akuaja.id program based on Microsoft Excel. By using this program, it is expected that the process of recording and preparing financial reports becomes more practical and useful in supporting better business decision-making.